Programmer Selection Using Modified Fuzzy Mamdani Method - Manan, Abdul; Wiley, Victor; Lucas, Thomas (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 2 August 2019, 2019)
Selection of candidate of the programmer is a complex and tiring process. Software development manager must work hard to guarantee that only qualified candidates will be selected. This study the parameters needed by the programmer are proper and adequate knowledge, skills, attitudes, and productivity. Knowledge, skills, attitudes, and productivity are the four competencies that every programmer must-have. The four components above are very important in developing an IT company. This study proposes a classification model of programmer selection based on certain criteria, parameters, and attributes. This study modifies the Fuzzy Mamdani Method as the approach for determining the feasibility of the programmer. The proposed model has satisfied result of percent of accuracy with 75.57% level. The result indicates that the proposed model has produced a sufficient solution to be used in the real situation for selecting the feasible programmer.